Effects of amnioinfusion in meconium-stained amniotic fluid complicating pregnancy - Emil Josephine, J. Princy; Shanthi, M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: In our country a major cause of perinatal mortality and morbidity is MAS (MAS) in new-born. The aim of the study was to assess feto-maternal outcome following intrapartum amnioinfusion in patients with meconium-stained amniotic fluid and Neonatal intensive care unit (NICU) admission following intrapartum amnioinfusion in patients with meconium stained amniotic fluid. Methods: This prospective observational study was conducted on 200 patients with pregnancy at or beyond 37 weeks in active labour with moderate to thick meconium stained liqour following spontaneous rupture or Artificial rupture of membranes (ARM). In 100 patients amnioin fusion was performed and rest 100 were in control group. Continuous electronic fetal heart rate (FHR) monitoring was performed. Emergency lower segment caesarean section (LSCS) was done when fetal bradycardia was recorded or in case of non-progress of labor. Fetomaternal outcome will be noted. Results: In present study there were more cases of fetal distress in the control group (38) compared with the amnioinfusion group (24). 34 patients in the amnioinfusion group and 38 patients in the control group were delivered by LSCS. The incidence of MAS in amnioinfusion group was 3 in number where as 14 in number of control group. Similarly, in our study 13 neonates of amnioinfusion group and 31 neonates of control group were needed admission in NICU. Conclusions: Intrapartum amnioinfusion in meconium-stained amniotic fluid by diluting the meconium and by decreasing the cord compression decreases the incidence of foetal distress and there by decreases incidence of MAS in neonates and NICU admission, these all leads to decrease the incidence of maternal and perinatal morbidity and mortality.